Synthesis and in vitro toxicity of 4-MTA, its characteristic clandestine synthesis byproducts and related sulphur substituted a-alkylthioamphetamines - WILLIAMS, DAVID CLIVE; KAVANAGH, PIERCE VALENTINE; CLOONAN, SUZANNE; MEEGAN, MARY JANE; O'BRIEN, JOHN EUGENE; CORRIGAN, DESMOND (My University, 2010)
4-Methylthioamphetamine (4-MTA) is recognised as a 3,4-methylenedioxymethamphetamine (MDMA)-like drug of abuse. Such amphetamine-type drugs often contain byproducts of uncontrolled, illegal clandestine synthetic processes. We report the isolation and structural identification of a number of novel pyridines, dihydropyridone and N,N-di(1-aryl-2-propyl) amines as route-specific byproducts associated with clandestine synthesis of 4-MTA and related amphetamines. We report the in vitro cytotoxicity of 4-MTA, its synthesis byproducts together with some structurally related sulphur substituted ?-alkyl phenethylamines in cell lines overexpressing human monoamine transporters as well as in a primary neuronal cell line model and a dopaminergic neuroblastoma cell line. 4-MTA along with a number of other structurally related amphetamine derivatives and synthetic impurities were found to be cytotoxic to these cells within pharmacologically defined concentrations implying that 4-MTA is a cytotoxic agent in vitro and therefore might have the potential to be a neurotoxic agent in vivo.
PUBLISHED
Keywords: Biochemistry